Spontaneously Improving Occipitocondylar Hyperplasia: A Case Report - Nagy, Laszlo; Ray, Coby (Journal of Neurological Surgery Reports, 2014)
This case report presents a pediatric patient with the extremely rare craniovertebral junction anomaly of occipitocondylar hyperplasia. This 4-year old boy presented with macrocephaly and mild to moderate pontomedullary compression from the unilateral occipitocondylar hyperplasia. Based on the asymptomatic clinical presentation, it was decided to follow the patient with serial magnetic resonance images without surgical intervention. Upon further imaging the occipitocondylar hyperplasia spontaneously resolved. This case report offers watchful waiting as an alternative treatment approach to surgical intervention as was reported in the literature previously. Possible pathophysiologic mechanisms are also briefly explored.
Keywords: hyperplasia; occipital condyle; occipitocondylar; skull base